2003
DOI: 10.1128/aem.69.9.5045-5050.2003
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Natural and Synthetic Isoflavonoids by Two Recombinant Microbial Enzymes

Abstract: Isolation and synthesis of isoflavonoids has become a frequent endeavor, due to their interesting biological activities. The introduction of hydroxyl groups into isoflavonoids by the use of enzymes represents an attractive alternative to conventional chemical synthesis. In this study, the capabilities of biphenyl-2,3-dioxygenase (BphA) and biphenyl-2,3-dihydrodiol 2,3-dehydrogenase (BphB) of Burkholderia sp. strain LB400 to biotransform 14 isoflavonoids synthesized in the laboratory were investigated by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…Helium served as carrier gas. The mass spectrometer was operated in the electron impact ionization mode at 70 eV as described (Seeger et al, 2001(Seeger et al, , 2003. The following AHL standards were purchased from Fluka: N-hexanoyl-DL-homoserine lactone (AHL-C 6 ), N-octanoyl-DLhomoserine lactone (AHL-C 8 ) and Ntetradecanoyl-DL-homoserine lactone (AHL-C 14 ).…”
Section: Purification and Identification Of Ahlmentioning
confidence: 99%
“…Helium served as carrier gas. The mass spectrometer was operated in the electron impact ionization mode at 70 eV as described (Seeger et al, 2001(Seeger et al, , 2003. The following AHL standards were purchased from Fluka: N-hexanoyl-DL-homoserine lactone (AHL-C 6 ), N-octanoyl-DLhomoserine lactone (AHL-C 8 ) and Ntetradecanoyl-DL-homoserine lactone (AHL-C 14 ).…”
Section: Purification and Identification Of Ahlmentioning
confidence: 99%
“…Isoflavonoids ( ) are one of the main subclasses of flavonoids ( ) which contain C6-C3-C6 carbon skeleton based on 3-phenylchroman [1]. They are widely distributed in many plants [2,3] and in various common foods which are particularly abundant in seeds and other parts of leguminous plants [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The ␣ subunit is the one involved in the catalytic activity. It comprises two domains; the Rieske domain containing a 2Fe-2S Rieske cluster receives the electrons from BphF and transfers them to the catalytic mononuclear iron center of the catalytic domain (7).Several investigations have shown that BPDO can metabolize flavonoids (4,15,29,30). These plant secondary metabolites (PSMs) are regarded as very promising for the prevention and treatment of cancers (26) and cardiovascular diseases (35).…”
mentioning
confidence: 99%